Penerapan Teknologi Digital Pada Pendidikan Matematika Pasca Pandemi Covid 19 - Novi Marliani; Idha isnaningrum (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
In the world of education, digital technology is not only a learning tool, but also a multidimensional concept. Educational Technology, especially mathematics education, is an ethical study and practice in an effort to facilitate learning and improve performance by creating, using, managing appropriate technological processes and resources. After the pandemic, learning technology is still used during online learning, such as using Google Meet, Zoom, Google Classroom and others, or during offline learning. Learning is very effective and optimal if the use of media is measurable, because the use of media is very meaningful if the media can provide more benefits, with the presence of media students are more stimulated in carrying out education. The type of research used in this research is literature study or library research. This type of research is used by researchers to obtain data and information by examining written sources such as scientific journals or proceedings that are relevant to the title to be researched. The stages carried out include identifying, reviewing, evaluating and interpreting the relevant articles and literature used.